Modifying structural polymorphs and tuning electronic properties in pressure-stabilized binary Ir–Sb phases. Issue 33 (20th May 2020) - Liu, Siyuan; Zhou, Dan; Cui, Manai; Xu, Jing; Ma, Xuejiao; Cheng, Yuheng; Jin, Zhexue; Liu, Yanhui
Abstract : Several pressure-stabilized binary Ir–Sb phases have been identified. The chemical bonding states are dramatically modified by the pressure effect. A pressure-induced electronic topological transition has been identified in Ir2 Sb. Abstract : The search for novel structures and chemical stoichiometry of binary Ir–Sb compounds is of great importance in view of their catalytic applications. Based on the results of swarm structure searching technique combined with density functional theory, we proposed the hitherto unknown Ir–Sb phase diagram in a wide pressure range with various chemical compositions. Besides two ambient pressure phases of IrSb3 -Im3̄ and IrSb2 - P 21 / c, five novel phases of IrSb- C 2/ c, IrSb- P 1̄, IrSb2 - P 4̄21 m, IrSb2 - I 4/ mmm and Ir2 Sb- Pmmn were identified at high pressures. The phonon dispersion curves reveal that these phases are all dynamically stable. The calculated electronic results show that a mixed behavior of covalent, ionic and metallic bonds simultaneously exits in these novel phases. A pressure-induced electronic topological transition in Ir2 Sb- Pmmn phase occurs according to the theoretical electronic band structures, while is not shown in other stoichiometries of the Ir–Sb system. Our work provides a potential opportunity for experimental synthesis of crystal structures with different chemical stoichiometries of the binary Ir–Sb system.